PENGARUH DIGITALISASI, ENTREPRENEURIAL MARKETING DAN EXPERIENTIAL MARKETING TERHADAP KEPUASAN KONSUMEN GENERASI MILLENIAL DI SAKURA HILLS TAWANGMANGU - Salsabillah, Hanifah Dwi; Pujiani, Dewi (Widya Dharma Journal of Business - WIJoB, 2024)
In this study, the author aims to detirment, test and develop the influence of digitalization, entrepreneurial marketing and experiential marketing on millennial generation consumer satisfaction in Sakura Hills Tawangmangu. The method used in this study uses a quantitative approach with a descriptive method. The method used in sampling in this study is non-probability sampling with accidental sampling method. The determination of the sample is based on chance. The sample used in this study were 100 respondents. The data collection carried out in this study is primary data with a survey method using written questions in the form of a questionnaire. Analysis of the data used in this study is multiple linear regression test, t test, F test, calculations performed using the SPSS test. Digitalization, entrepreneurial marketing and experiential marketing have a positive and equal effect on consumer satisfaction of the millennial generation in Sakura Hills. Digitalization has a positive and significant impact on millennial generation consumer satisfaction in Sakura Hills. This means that if the digitization system is improved, visitor satisfaction will increase. Entrepreneurial marketing has a positive and significant impact on millennial generation consumer satisfaction in Sakura Hills. This means that if the manager develops opportunities based on the needs and desires of today's millennial generation consumers, then consumer satisfaction will be created. Experiential marketing has a positive and significant effect on millennial generation consumer satisfaction in Sakura Hills. This means that if the quality of service is improved, it will create a memorable experience and a feeling of pleasure in visiting.